NKT cells enhance CD4+ and CD8+ T cell responses to soluble antigen in vivo through direct interaction with dendritic cells. - Hermans, I; Silk, J; Gileadi, U; Salio, M; Mathew, B; Ritter, G; Schmidt, R; Harris, A; Old, L; Cerundolo, V (2003)
Modification in the function of dendritic cells (DC), such as that achieved by microbial stimuli or T cell help, plays a critical role in determining the quality and size of adaptive responses to Ag. NKT cells bearing an invariant TCR (iNKT cells) restricted by nonpolymorphic CD1d molecules may constitute a readily available source of help for DC. We therefore examined T cell responses to i.v. injection of soluble Ag in the presence or the absence of iNKT cell stimulation with the CD1d-binding glycolipid alpha-galactosylceramide (alpha-GalCer). Considerably enhanced CD4(+) and CD8(+) T cell responses were observed when alpha-GalCer was administered at the same time as or close to OVA injection. This enhancement was dependent on the involvement of iNKT cells and CD1d molecules and required CD40 signaling. Studies in IFN-gammaR(-/-) mice indicated that IFN-gamma was not required for the adjuvant effect of alpha-GalCer. Consistent with this result, enhanced T cell responses were observed using OCH, an analog of alpha-GalCer with a truncated sphingosine chain and a reduced capacity to induce IFN-gamma. Splenic DC from alpha-GalCer-treated animals expressed high levels of costimulatory molecules, suggesting maturation in response to iNKT cell activation. Furthermore, studies with cultured DC indicated that potentiation of T cell responses required presentation of specific peptide and alpha-GalCer by the same DC, implying conditioning of DC by iNKT cells. The iNKT-enhanced T cell responses resisted challenge with OVA-expressing tumors, whereas responses induced in the absence of iNKT stimulation did not. Thus, iNKT cells exert a significant influence on the efficacy of immune responses to soluble Ag by modulating DC function.